(untitled) (Pedagogical Horizons, 2024)
The article addresses the interdisciplinary connection between art and theater education. From the perspective of aesthetic education, the authors attempt to create a meaningful connection between the two fields, which they first develop theoretically and then illustrate using a practical example. The example itself was developed as part of the international Erasmus project ACIIS - Academy for creative, innovative and inclusive schools.